(untitled) (Research, Society and Development, 2023)
The third sector consists of non-profit and non-state entities, which develop and offer goods and services directed to the well-being of a society or community. This research is delimited on the theoretical aspects that refer to accounting in the Third Sector, especially to schools, the objective was to know and identify the origin and application of government resources intended for public schools of the municipal school system of Augustinópolis - TO. Methodologically, this article is an exploratory study, of a documentary nature with a qualitative approach, seeking to identify how these governmental resources are being applied within these school units. To the results, in relation to the origin and application of resources, it was noted that not all school units have an Association of Parents and Teachers, to which are inserted the Executing Units that are responsible for receiving and applying the resources coming from the government. In addition, it was noticed that the resources applied for educational purposes in the public teaching units come from taxes, such as federal, state and municipal taxes. In short, it is considered that this article will contribute significantly to the general public, since it analyzes from the origin of government resources to their applicability in basic education.